Ethnoscience in the Digital Age: A Systematic Review of Pedagogical Strategies for Scientific and Digital Literacy Development - Reza Akmar; Sudarmin Sudarmin; Edy Hafizan; Dwi Septiana Sari (FKIP Universitas Lampung, 2026)
In the 21st century, achieving proficiency in both scientific and digital literacies is crucial for effective societal participation and addressing complex global challenges. However, a significant cultural disconnect often persists in formal science education, marginalizing students' indigenous knowledge. This systematic literature review aims to investigate the efficacy of ethnoscience-based instruction in bridging this gap and enhancing students’ scientific and digital literacies within the Indonesian educational context. Following PRISMA guidelines, a systematic search was conducted in Google Scholar, Scopus, Dimensions, and ERIC. This process identified 28 eligible studies published between 2016 and 2025. Data were analyzed and compared using reported gain scores to evaluate the impact of various instructional interventions. The findings reveal that research in this field is predominantly characterized by Research and Development (R&D) designs (60%), with a primary focus on the secondary school level. The analysis demonstrates that ethnoscience serves as a powerful pedagogical bridge, linking students' local cultural backgrounds to modern scientific concepts. While publications are increasing, a significant disparity exists between the widespread focus on scientific literacy and the emerging, yet underdeveloped, area of digital literacy. Interventions that integrate ethnoscience with digital modalities are effective for general knowledge acquisition but are limited in fostering higher-level scientific attitudes and inquiry when used without a robust pedagogical framework. The results indicate that integrating ethnoscience into established learning models, particularly Project-Based Learning (PjBL) and Problem-Based Learning (PBL), yields significantly more holistic outcomes compared to media-only interventions. These models are uniquely effective in promoting complex competencies, including scientific inquiry, citizenship literacy, and cultural awareness. This study concludes that future pedagogical practices should prioritize structured, model-based integration to fully harness the potential of ethnoscience for comprehensive 21st-century skill development. Keywords: ethnoscience, scientific literacy, digital literacy, systematic review.